Google Earth y la enseñanza-aprendizaje en Ciencias Naturales del séptimo grado de la Escuela de Educación Básica Particular “Timoteo”, 2021-2022. - Arias Yaure, Lizbeth Isabel (2022)
The research is directed to the study of use of Google Earth and the teaching-learning of Natural Sciences. Therefore, the general objective sets up was: Contribute to the teaching-learning process in the students of the seventh grade in the Natural Sciences subject of the “Timoteo" Private Basic Education school of the Loja city, throughout the use of the Google Earth application, to improve the educational process. In addition, three specific objectives were determined, as first; identify the main benefits by using the Google Earth technological tool in the teaching-learning process in the Natural Sciences subject; in second place; determine the impact of the Google Earth application throughout the demonstration technique in the Natural Sciences subject; and finally, to propose a didactic guide in order to guarantee better levels of learning with the use of Google Earth in the Natural Sciences subject, in the students of seventh of the "Timoteo" Private Basic Education school in the Loja city. The present research work had a qualitative-quantitative approach, of a descriptive type with a quasi-experimental design. Among the main methods which were used we have; scientific method, statistical method, descriptive method. Also, the following techniques were used: direct observation, survey, interview, demonstration technique, evaluation technique. For this, the type of non-probabilistic sampling was used in which sixteen people participated, including fifteen students and the teacher. Finally, it can say that using Google Earth in Natural Sciences is favorable in the teaching-learning process, therefore a didactic guide was built from this technological tool to strengthen the teaching learning process in this subject, whose results were relevant thanks to the demonstration technique applied in the classroom. Keywords: Google Earth, Natural Sciences, teaching-learning, teacher, student.